Mesa distrital del graffiti (2020)
Within what constitutes the project called District Graffiti Table, which arises in order to bring solutions to the situation that the San Felipe neighborhood presents in terms of urban art that invades and enriches the sector. Primarily focusing on the main creators of this ephemeral art manifestation, the graffiti artists, who in search of expressing their art, disagree with the residents of the neighborhood, while showing great empathy with the artists of the area. This dichotomy only exhibits the state of informality in which urban art artists are in the city of Bogotá, even more so considering that they belong to a middle and lower socio-economic class, where this becomes the argument of greater importance to solve, given the lack of participation spaces within the city for these young people. Identifying the above, it aims to improve the living conditions of urban artists, facilitating access to education in their art, decent housing and remuneration for their craft, while seeking artistic potential in the San Felipe neighborhood, consolidating it as the Bogotá's artistic district and eliminating distinctions between formal and informal artists